Malaysia tourism network games / Christopher Yip Wai Hon - Christopher Yip , Wai Hon (2006)
Web-based Public Information Systems of the kind common in tourism do not satisfy the needs of the customer because they do not offer a sufficiently flexible linking environment capable of emulating the mediation role of a tourist adviser. Much literature has argued that interactive engagement in a computer medium is best demonstrated by games. With this in mind, this paper suggests certain techniques that virtual environments (especially cultural heritage ones) can learn from game design. Thus, Malaysia Tourism Network games are introduced. Interesting animation show will be display when the player passes a stage. This can attract the player to explore Malaysia map and tourism spots and have fun.